Cardiovascular disease prevention in diabetes: uncertainties and ethics. (May 2014) - Shaw, Jonathan E; Fineberg, Daniel
SUMMARY: : In the last 20 years, there have been a large number of large clinical trials that have informed and improved clinical practice in regard to cardiovascular disease prevention in diabetes. Despite this, there remain a number of areas of uncertainty, some of which are regularly encountered in daily practice. The value of glucose lowering in the prevention of cardiovascular disease is unproven, and the potential for newer glucose-lowering agents to address this gap is uncertain. Although the overall value of blood pressure lowering is well established, the appropriate blood pressure targets remain controversial. Ethical issues arise from this uncertainty, and relate to the means of translating evidence for the average patient into action for an individual, and how to synthesize conflicting evidence.